Describing the Stereotype Lift efforts of librarians: A case study of female librarians - Montealto, Fritzie Niez; Ansao, Glory Mae Salinas; Naparan, Janus Agustero; Encarnacion, Philipcris (Daluang: Journal of Library and Information Science, 2024)
Purpose. This research delves into the stereotype-laden environment faced by female librarians and the efforts undertaken to counteract these stereotypes. In situations where the worth or ability of an outgroup is questioned, stereotype lift makes people perform better.Methodology. This study utilized qualitative research with a single-case study approach. The participants of the study were five female librarians working within the Zamboanga Peninsula, Philippines. The interview guide questions were used to gather their responses alongside observation and some documents. Permission from the school president was secured first before going to the library, which was also similarly done for online participants. The librarians were in terms of their physical characteristics, emotions, and how they catered to the patrons and researchers. In addition, ocular visits were conducted in which researchers took photos of what could help support the observation. After having the necessary data, Category Construction was utilized to analyze it.Results and discussion. The findings revealed the stereotypes the respondents received: stern and sedentary workers. These stereotypes unveiled how it affects their work performance by remaining unaffected and becoming more approachable. With these effects encountered, the female librarians were able to come up with two strategies for dealing with the stereotypes: remaining calm and positively changing oneself. The librarians also promoted equity, diversity, and inclusion by providing equal treatment to all and organizing a club for book lovers.Conclusions. The effect of stereotypes on librarians was not manifested since some of them perceived it as usual, while some let it change them to better librarians.